Preferential treatment, class size and numerical ability as correlates of achievement in senior secondary economics in Ogun state, Nigeria. (2012)
" Economics is a core social science subject offered by most science, art and social science students, but the students performance in the subject at final examinations has not been encouraging. This study therefore investigated the relationship of preferential treatment, class size and numerical ability with achievement in Senior Secondary Economics. The study is a survey and a sample of300 senior secondary school students were selected from two local governments of Ogun East senatorial district, using multi-stage cluster sampling technique. Three valid and reliable instruments were used for data collection and these are: The Student Preferential Treatment Scale (SPTS),Numerical Ability Test (NAT) and Economics Achievement Test (EAT). Four research questions were raised and answered in this study. Data collected were analysed using both descriptive and inferential statistics. The results revealed that all the independent variables were positively correlated to the Economics achievement test in Economics. The findings also revealed that the three predictors jointly correlates positively with students' performance in Economics. Based on the findings of the study, it is recommended that the studen ts-teachers ratio should be improved upon, parents and teachers should assist students to develop their mathematical ability."